2013
DOI: 10.1021/ja312155v
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Self-Assembly in Water of Long Noncovalent Polymers by Nucleobase Analogues

Abstract: Molecular self-assembly is widely appreciated to result from a delicate balance between several noncovalent interactions and solvation effects. However, current design approaches for achieving self-assembly in water with small, synthetic molecules do not consider all aspects of the hydrophobic effect, in particular the requirement of surface areas greater than 1 nm(2) for an appreciable free energy of hydration. With the concept of a minimum hydrophobic surface area in mind, we designed a system that achieves … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
165
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 156 publications
(171 citation statements)
references
References 30 publications
4
165
0
Order By: Relevance
“…It is essential to address this significant gap in knowledge, since these interactions could collectively affect the outcome (e.g., polymer yields, sequence space, and length) of RNA polymerization, particularly in prebiotic environments that lack the biological tools responsible for regulation of RNA polymerization in modern biology. This line of inquiry complements recent explorations by others on molecular self-assembly in prebiotic environments (Deamer et al, 2006), nucleotide aggregation (e.g., Raszka and Kaplan, 1972;Rymden and Stilbs, 1985;Eimer and Dorfmuller, 1992), and self-assembly of nucleobase analogues (Cafferty et al, 2013).…”
Section: Introductionsupporting
confidence: 65%
“…It is essential to address this significant gap in knowledge, since these interactions could collectively affect the outcome (e.g., polymer yields, sequence space, and length) of RNA polymerization, particularly in prebiotic environments that lack the biological tools responsible for regulation of RNA polymerization in modern biology. This line of inquiry complements recent explorations by others on molecular self-assembly in prebiotic environments (Deamer et al, 2006), nucleotide aggregation (e.g., Raszka and Kaplan, 1972;Rymden and Stilbs, 1985;Eimer and Dorfmuller, 1992), and self-assembly of nucleobase analogues (Cafferty et al, 2013).…”
Section: Introductionsupporting
confidence: 65%
“…Further, base analogs modified for enhanced stacking form paired, free stacks thousands of residues in length (Cafferty et al 2013). A completely paired template-nucleotide complex like the calculated one (Fig.…”
Section: Runaway Stacksmentioning
confidence: 65%
“…Hud et al have demonstrated self--assembly of CA with hydrophilic derivatives of 2,4,6--triaminopyrimidine (TAP) in water, including a monomeric TAP--ribose derivative 46 . These mixtures produced hexameric rosettes that stacked into long fibers with a similar diameter to the d(A n ):CA structure described here.…”
Section: Investigation Of Fiber Structurementioning
confidence: 99%